A voz universitária – uma estratégia de promoção à saúde para os moradores da Região Transamazônica e Xingu - DANTAS, Ana Karla da Silva (2025)
Introduction: According to the International Conference on Health Promotion, held in Ottawa, Canada, in 1986, Health Promotion consists in the process of empowering the community to act to improve their quality of life and health, including greater participation in the control of this process . Thus, actions aimed at Health Promotion have their pillars in aspects that permeate quality of life. Currently, radio is a popular medium that makes up the daily routine of Brazilians, with the diversified and playful language that has increased its popularity over the last few decades. In this way, the dissemination of health education through the local radio program will contribute to the formation and development of people's critical awareness in relation to health problems, as well as to stimulate the search for a solution and the organization for collective action, so that everyone becomes agents of transformation in the community. Objective: Disseminate information on health, environment, well-being and leisure to residents of the Transamazônica and Xingu region. Methodology: This is an extension project, which was carried out through a partnership with Rádio Vale do Xingu FM 93.1 MHz, located in the municipality of Altamira-Pará, and addressed health education activities with the aim of bringing riverside community, rural and urban community information focused on health, well-being and leisure. In addition to publicity on local radio, the project's publicity platforms included the most used social networks at the moment, such as: Facebook page with Web-radio, Instagram and Telegram group. The radio programs, educational campaigns and other activities carried out by project members were publicized.